Nurses’ attitudes toward patient death and coping strategies: a cross-sectional study in Poland - Cybulska, Anna Maria; Czeryna, Izabela; Derezińska, Aleksandra; Nowak, Marta; Majkowska, Lilianna; Schneider-Matyka, Daria; Grochans, Elżbieta; Rachubińska, Kamila (Frontiers in Public Health, 2025)
IntroductionNurses working in end-of-life care are frequently exposed to patient death, which shapes both their attitudes toward death and the coping strategies they adopt. This study aimed to explore nurses’ attitudes toward death and the coping mechanisms they employ in the hospital setting.MethodsData were collected through a diagnostic survey incorporating a self-designed questionnaire and standardized instruments: the Death Attitudes Profile Questionnaire and the MINI-COPE Scale.ResultsThe study included 315 nurses (85.7% women) with a mean age of 40.5 years. Most participants lived in towns of up to 100,000 residents (70.1%) and held a master’s degree (53.3%). The predominant attitude toward death was Natural Acceptance (5.40 ± 0.97 point). The most commonly used coping strategies were Preoccupation with Other Activities (1.98 ± 0.75 point), Active Coping (1.88 ± 0.69 point), and Planning (1.87 ± 0.77 point). Greater exposure to patient death was associated with higher levels of Natural Acceptance and Escape Acceptance, alongside lower levels of Death Avoidance. Negative emotions most frequently reported were sadness (62.9%), compassion (57.5%), and helplessness (47.0%), underscoring the emotional burden of end-of-life care.ConclusionNurses frequently experience negative emotional responses to patient death, emphasizing the need for accessible psychological support. Sociodemographic and professional factors significantly influence both attitudes toward death and stress-coping strategies, highlighting the importance of targeted interventions to strengthen resilience among nursing staff in end-of-life care.